Macrophages: A communication network linking Porphyromonas gingivalis infection and associated systemic diseases - Lin, Jie; Huang, Dingming; Xu, Hongwei; Zhan, Fenghuang; Tan, XueLian (Frontiers in Immunology, 2022)
Porphyromonas gingivalis (P. gingivalis) is a Gram-negative anaerobic pathogen that is involved in the pathogenesis of periodontitis and systemic diseases. P. gingivalis was recently detected in rheumatoid arthritis (RA), cardiovascular disease, and tumors, as well as Alzheimer’s disease (AD), and the presence of P. gingivalis in these diseases is correlated with a poor prognosis. Macrophage is a major innate immune cell and modulates immune responses against pathogens, however multiple bacteria have evolved the ability to evade or even subvert the macrophage immune response and subsequently promote the disease initiation and progression. P. gingivalis as a keystone pathogen of periodontitis has received increasing attention with respect to the onset and development of systemic diseases. P. gingivalis induces macrophage polarization and inflammasome activation, and evasion of immune response, which play important roles in promoting inflammatory diseases, autoimmune diseases, and tumor development. In this review, we summarize recent discoveries that the interaction of P. gingivalis and macrophages in relevant disease development and progression, such as periodontitis, atherosclerosis, RA, AD, and cancers, aiming to provide an in-depth mechanistic understanding of this interaction and potentially therapeutic strategies.